Effect of particle morphology on microstructural, mechanical and bioactivity properties of injection molded Ti-6Al-4V Powder - (:unkn) unknown (My University, 2013)
This study describes the effect of particle morphology on the microstructural, mechanical and bioactivity properties of injection molded Ti64 (Ti-6Al-4V) powder. Ti64 powders irregular and spherical in shape were injection molded with wax based binder. The critical powder loadings for injection molding were 62.5 and 50 vol. % for spherical and irregular powders, respectively. Debinding was performed by solvent and thermal methods. After debinding the samples were sintered at 1300 °C for 10 h. under high vacuum. Metallographic studies were conducted to determine densification and the corresponding microstructural changes. Sintered samples were immersed in a simulated body fluid (SBF) with elemental concentrations that were comparable to those of human blood plasma for a total period of 15 days. Both materials were implanted in fibroblast culture for biocompatibility evaluations. The results show that both spherical and irregular powders could be sintered to a maximum theoretical density. Maximum tensile strength was obtained for spherical shape powder sintered at 1300 °C for 10 h. The tensile strength of the irregular shape powder sintered at the same temperature was lower due to higher porosity. Finally, mechanical tests show that the irregular shape powder has lower mechanical properties than spherical shape powder. The results of this study showed that sintered spherical and irregular Ti64 powders exhibited high mechanical properties and good bio-activity properties. In particular, these materials can be used in some bio applications.